1986
DOI: 10.1152/ajpregu.1986.250.3.r383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet and photoperiod on NE turnover and GDP binding in Siberian hamster brown adipose tissue

Abstract: This experiment examined the effects of diet and photoperiod on food intake, body weight, and brown adipose tissue (BAT) activity in female Siberian hamsters (Phodopus sungorus sungorus). BAT function was assessed by measuring both the sympathetic nervous system activity of BAT [estimated by the rate of norepinephrine (NE) turnover] and BAT thermogenic activity (estimated by GDP binding to BAT mitochondria). Nineteen weeks of high-fat feeding in long photoperiod [16:8 light-dark cycle (LD)] caused a 20% increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The Siberian hamsters are a natural model of adiposity that, when fed a high-fat diet, do not increase their caloric intake and so do not gain additional weight. Even in longterm high-fat diet studies where some increase in food intake can be observed in Siberian hamsters, this does not result in weight gain, rather the animals increase thermogenesis via increased sympathetic nervous system (SNS) activation of brown fat (McElroy et al 1986). Although hamsters have a different biology from mice and rats, which is a reflection of their evolution and ecology, they cannot be considered to be any less valid as a model for understanding fundamental mechanisms of action of hormones than other rodents; indeed, using a variety of animal models has overall translational benefits (Ebling 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Siberian hamsters are a natural model of adiposity that, when fed a high-fat diet, do not increase their caloric intake and so do not gain additional weight. Even in longterm high-fat diet studies where some increase in food intake can be observed in Siberian hamsters, this does not result in weight gain, rather the animals increase thermogenesis via increased sympathetic nervous system (SNS) activation of brown fat (McElroy et al 1986). Although hamsters have a different biology from mice and rats, which is a reflection of their evolution and ecology, they cannot be considered to be any less valid as a model for understanding fundamental mechanisms of action of hormones than other rodents; indeed, using a variety of animal models has overall translational benefits (Ebling 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological stimuli promote SNS activity in a tissue-specific manner; therefore, activation of SNS outflow to one organ does not necessarily represent outflow to all organs (29). Measurements of norepinephrine turnover (NETO) in specific tissues has been used as a measure of site-specific sympathetic activity in conditions such as fasting (28) and seasonal changes in energy balance in hibernating animals (27). Collins et al (7) found only a small nonsignificant increase in NETO to retroperitoneal (RP) white adipose tissue of mice given an intraperitoneal injection of leptin, despite a significant increase in intrascapular brown adipose tissue (IBAT) NETO.…”
mentioning
confidence: 99%
“…Additionally, there might be a different response to a high-fat diet for the animals exhibiting resistance to diet-induced obesity Peacock et al 2004). For example, a high-fat diet increased activity in Bank voles (Peacock & Speakman 2001;Peacock et al 2004) and meadow voles (Dark & Zucker 1983;Meek et al 1995), and thermogenic capacity in Siberian hamsters (McElroy et al 1986). These results suggest that the resistance to diet-induced obesity observed in photoperiodic animals is likely due to the increases in energy expended on metabolism and/or activity.…”
Section: Bmr and Nst And Ucp1 Levelmentioning
confidence: 99%
“…In the present study, we determined the effect of short day and high-fat diet on body-weight gain, thermogenesis, body fat mass, body compositions, energy budgets and BAT UCP1 expression to test the hypothesis that A. chevrieri showing short-day induced decreases in body mass and body fat mass, similar with Siberian hamsters (Phodopus sungorus) (Pallas, 1773) (McElroy et al 1986), Shaw's jird (Meriones shawi) (Milne-Edwards, 1867) (El-Bakry et al 1999) and meadow voles (Microtus pennsylvanicus) (Pallas, 1773) , should be resistant to the high-fat diet-induced obesity.…”
Section: Introductionmentioning
confidence: 99%